Tillandsia tenuifolia L. (Bromeliaceae) as nesting substrate for social wasps of the genus Mischocyttarus (Vespidae, Polistinae) in the cerrado biome - Leonardo Dutra Barbosa; Maria Luiza Simões Silva; Fernando Gonçalves de Aguiar Crispim; Gabriel de Castro Jacques; Marcos Magalhães de Souza (Acta Biológica Catarinense, 2025)
The nesting substract selection by social wasps is related to the protection of colonies, either against predators or adverse weather conditions. Despite the growing number of studies on nesting, there is still limited information on the use of bromeliad species as substrates for social wasps. Therefore, the aim of this study is to report the use of Tillandsia tenuifolia L. (Bromeliaceae, Tillandsioideae) as nesting substrate for social wasps of the genus Mischocyttarus Saussure, 1853, in a cerrado area in the state of Minas Gerais, southeastern Brazil. Eleven colonies of wasps were recorded, including one of Mischocyttarus drewseni Saussure, 1857, three of Mischocyttarus rotundicollis (Cameron, 1912), two of Mischocyttarus mirificus (Zikán, 1935), two of Mischocyttarus wagneri (Buysson 1908), and three of Mischocyttarus sp. This genus of social wasps can build their nests in bromeliads, which protect their nests, either through camouflage or concealment, as a form of indirect defense, and these plants offer ideal conditions for this form of shelter.